17. yüzyıl mensur şehname tercümesi 200a- 230b - Karamanlıoğlu, Özgü (My University, 2006)
Eser, İstanbul Üniversitesi Merkez Kütüphanesi 6131 demirbaş numarasıyla kayıtlıdır. Üç cilt halinde ve tamamı 1778 varaktır. Ayrıca eserde minyatürlere yer verilmiş, her sayfası 25 satır olarak düzenlenmiştir. Üzerinde çalışılan I. cildin boyu 39, eni 24.5, kalınlığı 7.5 cm’dir. Eser hicri 1187 miladi 1773 yılında tamamlanmıştır. Kelime kelime bir tercüme değildir. Tez yazmanın 200a-230b varaklarını kapsamaktadır. Tez üç bölümden oluşmaktadır: Giriş, metin ve sözlük. Giriş bölümünde Firdevsî, Şehnâme, Şehnâme çevirileri ve üzerinde çalışılan yazmayla ilgili bilgiler verilmektedir. Metin kısmında sayfa ve satır numaraları belirtilmiş, günümüz noktalama işaretlerine göre noktalaması ve gerekli kısımlarda paragraflar yapılmıştır. Böylece eserden faydalanılması daha kolay hale getirilmek istenmiştir. Sözlük bölümünde eserin söz varlığını gösteren bir indeks hazırlanmıştır. Madde başı olarak kabul edilen kelimelerin altına o kelime ilgili ara madde, deyim ve birleşikler sıralanmış, madde başı ve ara maddelerin ikinci, üçüncü unsur olarak geçtiği maddelere (→) işareti ile göndermeler yapılmıştır. Eserdeki kelimelerin metinde geçtiği anlamları verilmeye çalışılmıştır.

The book is registered under fixture number 6131 at the Central Library of İstanbul University. It is composed of 3 volumes with total pages of 1778. Also miniatures have taken place in the book with each page designed in 25 lines. The length of the first volume on which the work is being carried on, is 39 cm, the width is 24.5 cm and thickness is based 7.5 cm. The work was complated in 1187 date based on Hegira, in 1773 date based on Christian Era; it is not translation word by word. The thesis includes the pages 200a-230b of the manuscript. This work is composed of three sections which are the introduction, the text and the dictionary. In the intoduction part, information about Firdevsî, Şehnâme, Şehnâme translations and the manuscript on which the work is carried on; is given. In the text, the page and line numbers are shown, designed according to today’s punctuation marks and the necessary parts paragrapsh are created. In this way, it has been aimed to get benefit of the work more easily. In dictionary, an index is prepared which shows are vocabulary of the book. The wording accepted as the beginning (main) item as shown below the intermediary item, expression and composed wording related to that word. The items identified as second, third factors of the main or intermediary items have been referred with marking (→). The meanings of the words and compound forms in the book are tried to be explained. NDEKİLER.................................................................................I ÖN SÖZ............................................................................................II ÖZET................................................................................................III SUMMARY......................................................................................IV KISALTMALAR..............................................................................V GİRİŞ................................................................................................1 METİN..............................................................................................9 SÖZLÜK...........................................................................................84 TIPKI BASIM...................................................................................245 BİBLİYOGRAFYA..........................................................................308 ÖZ GEÇMİŞ.....................................................................................311
Keywords: Divan Edebiyatı_Şehname; Türk Dili